2011
DOI: 10.5664/jcsm.1064
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Psychomotor Vigilance Performance and Quality of Life in Obstructive Sleep Apnea

Abstract: Objective: Patients with obstructive sleep apnea (OSA) commonly have cognitive complaints, particularly in attention, and report decreased quality of life. We examined how vigilance and sustained attention, as assessed by the Psychomotor Vigilance Task (PVT), were related to quality of life after controlling for apnea severity and depression in subjects with OSA. Subjects and Methods: Fifty-seven patients with newly diagnosed and untreated OSA had their sleep monitored with polysomnography. Quality of life was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…The PVT is an objective measure of vigilance performance 43 and has been demonstrated to be sensitive to sleep loss and recovery regardless of cause. 44,45 For OSA, there is not good evidence of a clear dose-response relationship between the primary measure of sleep apnea severity (ie, AHI) and PVT as one might expect, 24,28,29 with the likely reason being that AHI is not highly correlated with daytime symptoms and functioning. However, measures of daytime sleepiness are related to the PVT in patients with OSA.…”
Section: Psychomotor Vigilance Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVT is an objective measure of vigilance performance 43 and has been demonstrated to be sensitive to sleep loss and recovery regardless of cause. 44,45 For OSA, there is not good evidence of a clear dose-response relationship between the primary measure of sleep apnea severity (ie, AHI) and PVT as one might expect, 24,28,29 with the likely reason being that AHI is not highly correlated with daytime symptoms and functioning. However, measures of daytime sleepiness are related to the PVT in patients with OSA.…”
Section: Psychomotor Vigilance Taskmentioning
confidence: 99%
“…The Psychomotor Vigilance Task (PVT) is a sustained attention and reaction time test that has seen widespread use in the study of sleep and circadian rhythms. [25][26][27][28] It has been demonstrated to be sensitive to deficits in alertness and sustained attention, both of which are commonly observed in patients with OSA, 24 as well as improvements in these domains resulting from treatment. [29][30][31][32] A number of studies have provided evidence that attentionrelated impairments resulting from OSA can significantly improve following treatment with CPAP.…”
mentioning
confidence: 99%
“…In another series of 135 consecutive patients with suspected OSA, ESS was associated with generic physical HRQL, but not the AHI or EEG arousal index [10]. Other referral series also fail to show a relationship between AHI and physical HRQL [5, 7, 11]. Given these findings and our own, there appears to be no clear association between OSA severity (as measured by AHI) and generic physical HRQL, even though subjective sleepiness (measured by the ESS) indeed is correlated consistently with HRQL.…”
Section: Discussionmentioning
confidence: 99%
“…The following sympathetic activation, with increased levels of catecholamines, leads to atherosclerosis and increased risk for cardiovascular morbidity and mortality . Psychosocial issues, such as depressive symptoms and poor self‐rated health, are also associated with OSA and affect both the patient and partner . A recent Swedish study found that 59% of middle‐aged primary care patients with diagnosed and treated hypertension had undiagnosed and untreated OSA .…”
Section: Introductionmentioning
confidence: 99%